Primary seismic refraction data during cruise RV SONNE SO258/2 (INGON), Indian Ocean off Sri Lanka, profile AWI-20170400 - Estella Weigelt; Wolfram H Geissler; Tabea Altenbernd-Lang; Wilfried Jokat; Reinhard Werner (PANGAEA, 2025)
As part of the research project INGON (a collaboration between the Alfred Wegener Institute and the GEOMAR), two offshore seismic refraction profiles were obtained during Sonne cruise SO258 to study the separation of India and Antarctica. The acquired data set covers data of 30 stations recorded with three different types of Ocean Bottom Seismometer (OBS)-systems: 12 LOBSTER and 2 NAMMU systems of the AWI belonging to the DEPAS pool (German Instrument Pool for Amphibian Seismology) and 20 OBS systems of GEOMAR. 21 instruments were deployed for profile AWI-20170400 at an average distance of 13.5 km. The profile extends in a NW-SE direction and crosses the proposed prolongation of the 85°E Ridge. Profiling started on 02 August 2017 at 84.24122°N, 1.12148°E, and ended on 03 August 2017 at 82.37525°N, 3.38.813°E. One OBS (station 407) could not be recovered, one OBS (station 421) did not return data, but all other OBS worked and could be synchronized with the GPS clock upon recovery such that skew values describing the clock drift are available for all stations. The data set provides primary data of OBS-stations concerning the refraction seismic profile AWI-20170400. It comprises (a) seismic station data in segy-format, (b) navigation data with date, time, coordinates, and shot-numbers, and (c) a table with general information on date, coordinates, equipment, data-format, acquisition and recording parameters, and other meta-data.